Objective biometric methods for the diagnosis and treatment of nervous system disorders - Torres, Elizabeth B. (Academic Press, an imprint of Elsevier, 2018)
Objective Biometric Methods for the Diagnosis and Treatment of Nervous System Disorders provides a new and unifying methodological framework, introducing new objective biometrics to characterize patterns of sensory motor control underlying symptoms. Its goal is to radically transform the ways in which disorders of the nervous system are currently diagnosed, tracked, researched and treated.iAThis bookiAintroduces new ways to bring the laboratory to the clinical setting, to schools and to settings of occupational and physical therapy. Ready-to-use, graphic user interfaces are introduced to provide outcome measures from wearable sensors that automatically assess in near real time the effectiveness of interventions. Lastly, examples of how the new framework has been effectively utilized in the context of clinical trials are provided.